The behaviour of Mortar Filled Double Skin Hollow Steel Columns / Clotilda Petrus, Lyn Dee Goh and Zulaikha Let - Petrus, Clotilda; Lyn, Dee Goh; Let, Zulaikha (2023)
Double Skin Hollow Mortar Filled Column (DSHMFC) is one of the composite columns that has been applied widely in civil engineering for its predominant mechanical behaviour. The hollow section in the column is to provide the space for service work such as piping and electrical conduit. These three specimens 300 mm DSHMFC columns were prepared with 65 mm, 75 mm, and 85 mm diameter of inner PVC tubes and 162.5 mm diameter of mild steel tube as outer skin. The study demonstrated the experimental investigation of DSHMFC acting as columns in compression with various diameters of the inner PVC tube. The space between the two skins was filled with mortar with a compressive strength of 42.5 MPa.